Autoimmune Hepatitis Associated with Immune Thrombocytopenic Purpura - Ito, Akihiro (Intern Med, 2017)
Although autoimmune hepatitis (AIH) is frequently complicated with chronic thyroiditis or other autoimmune disorders, reports on its association with immune thrombocytopenic purpura (ITP) are scarce. We herein describe a case of AIH associated with ITP. A 75-year-old Japanese woman was admitted to our hospital due to increased aminotransferase levels and severe thrombocytopenia. Elevated serum immunoglobulin G (IgG) was detected, and tests for platelet-associated IgG and anti-nuclear antibody were positive. Following the diagnosis of AIH-associated ITP, prednisolone treatment of 0.6 mg/kg/day resulted in a decrease in the aminotransferase levels and an increased platelet count.